Rancang Bangun Alat Cuci Tangan Nirsentuh sebagai Sarana Edukasi dan Pencegahan Covid-19 - Gunawan Dewantoro; Ignatius Jody; Imaddudin Abdurrahman; Ferdi Yansen; Hoeko Setyawijaya (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2020)
As the confirmed Covid-19 cases increase, the health promotion and disease-preventing actions become more prevalent in the society, including the proper handwashing campaign. Thus, contactless handwashing machines were constructed to educate the society how to wash hands complying with WHO standards. This machine integrated all the steps of proper handwashing processes, starting from wetting the hands, applying soap, rinsing the hands, and drying the hands, automatically without the need of physical contact. For each handwashing step, an instructional voice is produced to guide the hand washer. The outcome of this community service is the availability of contactless handwashing machines in several spots in Salatiga city, which at the same time serves as educational tools for the society.